Physiology and growth of newly bred Basmati rice lines in response to vegetative-stage drought stress - Waheed, Raheela; Deeba, Farah; Zulfiqar, Faisal; Moosa, Anam; Nafees, Muhammad; Altaf, Muhammad Ahsan; Arif, Muhammad; Siddique, Kadambot H. M. (Frontiers Media, 2023)
Basmati rice is inherently sensitive to various environmental stresses. Abrupt changes in climatic patterns and freshwater scarcity are escalating the issues associated with premium-quality rice production. However, few screening studies have selected Basmati rice genotypes suitable for drought-prone areas. This study investigated 19 physio-morphological and growth responses of 15 Super Basmati (SB) introgressed recombinants (SBIRs) and their parents (SB and IR554190-04) under drought stress to elucidate drought-tolerance traits and identify promising lines. After two weeks of drought stress, several physiological and growth performance traits significantly varied between the SBIRs (p ≤ 0.05) and were less affected in the SBIRs and the donor (SB and IR554190-04) than SB. The total drought response indices (TDRI) identified three superior lines (SBIR-153-146-13, SBIR-127-105-12, SBIR-62-79-8) and three on par with the donor and drought-tolerant check (SBIR-17-21-3, SBIR-31-43-4, SBIR-103-98-10) in adapting to drought conditions. Another three lines (SBIR-48-56-5, SBIR-52-60-6, SBIR-58-60-7) had moderate drought tolerance, while six lines (SBIR-7-18-1, SBIR-16-21-2, SBIR-76-83-9, SBIR-118-104-11, SBIR-170-258-14, SBIR-175-369-15) had low drought tolerance. Furthermore, the tolerant lines exhibited mechanisms associated with improved shoot biomass maintenance under drought by adjusting resource allocation to roots and shoots. Hence, the identified tolerant lines could be used as potential donors in drought-tolerant rice breeding programs, administered for subsequent varietal development, and studied to identify the genes underlying drought tolerance. Moreover, this study improved our understanding of the physiological basis of drought tolerance in SBIRs.